Analysis Zhang Ailing’s Novel (Red Rose And White Rose) Image Of The Characters And Story Plot - Yetty, Yetty; Rosemary, Rosemary (Lingua Cultura, 2011)
Zhang Ailing is a heterogeneous novel writer in China literature’s history. Almost of her life, she already wrote so many literature’s works. One of her famous novel is (Red Rose and White Rose). The story is describe the image of main figure’s character and his emotional. Writer wants use the characterization, complexity of personality and story plot these three aspect to analysis the novel’s figure looks, figure character and the story. This novel story is a complication relationship between the man and two women, red roses as her lover and white rose as her wife. About a man that in his standard life and emotional condition occur some contradiction. Writer use reference material and theory of novel writing to analysis Zhang Ailing (Red Rose and White Rose)‘s novel. The result of this analisys are the most important part in novel’s story is not only about the story plot but also the describtion of figure looks and characterization. Zhang Ailing in (Red rose and white rose) descbribtion is very spesific, the story become so interesting because of the Complementary of the figure looks, figure characterization and story plot, embraced each other, fully reflects the fictional reality of compromise and frustration.